Living Arrangements for Sex Offenders in Ohio: effects of Economics, Law, and Government Assistance Programs - Rolfe, Shawn M. (The prison journal, 2018)
Throughout the United States, Sex Offender Registration and Notification (SORN) laws have created housing issues for registered sex offenders (RSOs). As a result of SORN, many RSOs may need to rely on family members for their housing needs. This study, drawing on data from 188 adult male RSOs in Ohio, focused on two separate SORN laws (i.e., Megan’s Law and the Adam Walsh Act). The findings suggest that neither law influences RSOs’ living with family members. However, the results did conclude that an RSO’s income, receipt of government assistance, or being on probation/parole predicted the odds of living with family members. Policy implications of such findings are discussed.